Time-frequency parameters of wrist muscles EMG after an exhaustive freestyle test - Caty, V.; Rouard, A. H.; Hintzy, F.; Aujouannet, Y. A.; Molinary, F.; Knaflitz, M. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of this study was to investigate the effects of an exhaustive test on the EMG frequencies of 2 wrist muscles. Seven male international swimmers (22.6 ± 2.7 years, height 191 ± 4 cm, weight 82,7 ± 5,3 kg, 1.92 ± 0.09 m/s for the velocity on 100m) performed an exhaustive test of 4*50m freestyle. An EMG System was used to record the electrical activity of 2 wrist muscles: the M. flexor carpi ulnaris (FCU) and the M. extensor carpi ulnaris (ECU). The time-frequency treatment was done according to the Knaflitz'method. The instantaneous mean frequency (IMNF) was obtained for each stroke of each 50m. The mean IMNF was calculated for each 25m of each 50m. Results indicated for both muscles, a decrease of IMNF at the end of the intensive test indicating the attempt of fatigue and the high recruitments within the crawl stroke. Subjects' differences were observed which could support the individualization of the training process.